Analisis Kinerja Lalu Lintas Pada Simpang Empat Panton Labu Menggunakan Metode PKJI 2014 Analysis of Traffic Performance at the Panton Labu Interchange Four Using the PKJI Method 2014 - Deni Iqbal; Kumita (Fakultas Teknik - Universitas Al Muslim - Bireuen Aceh- Indonesia, 2025)
Highways are one of the infrastructures for smooth traffic in both cities and villages or other areas. The more rapid the development of an area or city, the busier the traffic flow. This is due to the increase in population income so that they are able to have their own vehicles. Because the increasing number of vehicles on the road will cause traffic jams which can affect the quality of the road service. Congestion and busy traffic often occur on roads or road intersections. Road intersections are places where traffic conflicts occur. To find out the problems and solutions, intersection performance research was carried out using the PKJI 2014 analysis method. Primary data collection included the geometric conditions of the intersection and traffic volume, while secondary data was the District Network Map. North Aceh and Population of North Aceh Regency. In analyzing intersection performance using the 2014 PKJI Method which includes Capacity, Degree of Saturation and Service Level which is seen based on the volume and capacity ratio values. The observation period was carried out for 3 days (Monday, Tuesday and Saturday) from 7:00 to 21.00 WIB, with the help of a writing instrument (form). Based on the survey results, the performance of the Panton Labu intersection is currently in an unstable zone, this can be seen from the value of the degree of saturation exceeding the PKJI 2014 requirements, causing inconvenience and traffic chaos, especially on Mondays with a traffic volume (Q) of 2447.7 cur/hour at approach width A with a degree of saturation of 0.94 < Ds = Max 0.85.